100 people who changed the world - Time, Inc. (New York Time Books, 2010)
A collection of 100 extraordinary figures who, by accident or design, changed the world.
Religious figures & philosopher kings -- Leaders, elected & not -- Scientists, inventors, & innovators -- Cultural icons.
At head of title: Life.
Keywords: Biography; World history -- Pictorial works